2001
DOI: 10.1097/00002030-200108170-00006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of baseline polymorphisms in RT and protease on outcome of highly active antiretroviral therapy in HIV-1-infected African patients

Abstract: The response of patients infected with African subtypes of HIV-1 to HAART appears to be independent of regime, HIV-1 clade and baseline polymorphisms. Non-B subtypes are fully sensitive to HAART and, accordingly, therapy should not be withheld from African patients for reasons of viral diversity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 18 publications
8
66
0
Order By: Relevance
“…In their study of patients of African origin who were infected with a non-B subtype of HIV-1 and were living in London, Frater et al 41 found no significant difference in the response to therapy among patients infected with subtype A, those infected with subtype C, and those infected with subtype D. In the Paediatric European Network for Treatment of AIDS (PENTA) 5 trial, 62 there was no significant difference according to HIV-1 subtype in the virologic response to treatment or in the frequency of development of resistance among children. Overall, it appears that HIV-1 subtypes do not effect major differences in the response to antiretroviral therapy.…”
Section: Response To Therapymentioning
confidence: 99%
“…In their study of patients of African origin who were infected with a non-B subtype of HIV-1 and were living in London, Frater et al 41 found no significant difference in the response to therapy among patients infected with subtype A, those infected with subtype C, and those infected with subtype D. In the Paediatric European Network for Treatment of AIDS (PENTA) 5 trial, 62 there was no significant difference according to HIV-1 subtype in the virologic response to treatment or in the frequency of development of resistance among children. Overall, it appears that HIV-1 subtypes do not effect major differences in the response to antiretroviral therapy.…”
Section: Response To Therapymentioning
confidence: 99%
“…The V6 54 variant showed a lesser effect on nelfinavir and AG1776 with an 18-and 8-fold increase in the K i value, respectively. Variant V6 84 showed a greater decrease in inhibitor susceptibility (235-fold) to ritonavir than did V6 46 and V6 54 . To our surprise, the addition of mutation I84V decreased the binding affinity of indinavir to a lesser extent than M46I and I54V, 540-and 34-fold less, respectively, and the affinity of nelfinavir was 96-fold less than that of the mutation M46I.…”
Section: Resultsmentioning
confidence: 90%
“…The K m , k cat , and k cat /K m parameters were determined for LAI, a pretherapy isolated protease (wild type), and seven variants, V6, V6 46 , V6 54 , V6 84 , V6 46/84 , V6 54/84 , and V6 46/54/84 , using a synthetic substrate that mimics the CA-p2 site of Gag (Table 3). The V6, V6 46 , V6 54 , and V6 84 variants all experienced a decrease in k cat /K m of 2-, 2-, 3-, and 10-fold, respectively, when compared to LAI ( Table 2). Variants V6 46/84 , V6 54/84 , and V6 46/54/84 showed a decrease in k cat /K m of 5-, 8-, and 6-fold, respectively, when compared to LAI.…”
Section: Resultsmentioning
confidence: 99%
“…A French cohort study of 416 adult patients, 24% of whom carried non-B subtypes, showed that at 3, 6 and 12 months after initiation of ARV therapy (first line (Bocket et al, 2005). Frater et al studied patients of African origin who were infected with a non-B subtype of HIV-1 and were living in London, and found no significant difference in the response to therapy (first line regimens, 50% PI-based regimens, 50% NNRTI-based regimens) among patients infected with subtypes A, C and D (Frater et al, 2001). Geretti and collaborators reported that patients infected with subtypes A, C, D and CRF02_AG were as likely to achieve viral load suppression (NRTI backbone: AZT+3TC or TDF+FTC or TDF+3TC or 3TC+d4T or d4T+ddI or ABC+3TC; third drug: EFV or NVP or RTV boosted PI) as those infected with subtype B and showed comparable rates of CD4 cell count recovery (Geretti et al, 2009).…”
Section: Impact Of Hiv-1 Diversity In Response To Antiretroviral Therapymentioning
confidence: 99%